Gestaltungsraum Hochschullehre : Potenziale nicht-traditionell Studierender nutzen - Klages, Benjamin; Bonillo, Marion, 1969-; Reinders, Stefan; Bohmeyer, Axel (Budrich UniPress Ltd, 2015)
With the "opening of universities" to "non-traditional students", education policy demands for far-reaching reforms are addressed to German universities. How do universities meet these demands and what curricular-didactical considerations result from them? The authors take up this question as a productive moment in development-oriented action based on didactics of higher education and explore the potential - both for changes and for stabilisations in the area of higher education teaching - in an exemplary manner. Against the background of the framework conditions of a university of applied sciences, they discuss the possibilities of a target group-specific, curricular-didactic further development of part-time, social-scientifically oriented study programmes and present further reflections